2021
DOI: 10.5858/arpa.2021-0175-oa
|View full text |Cite
|
Sign up to set email alerts
|

Subcategorization of T1 Bladder Cancer on Biopsy and Transurethral Resection Specimens for Predicting Progression

Abstract: Context.— Despite continued surveillance and intravesical therapy, a significant subset of patients with lamina propria–invasive bladder cancer (T1) will progress to muscle-invasive disease or metastases. Objective.— To analyze the value of pathologic subcategorization of T1 disease in predicting progression. Design.— Six substaging methods were applied to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Most studies revealed significant prognostic impact (disease recurrence, n=6 studies; disease progression, n=18 studies; recurrence-free survival, n=6 studies; progression-free survival, n=13 studies; cancer-specific survival, n=7 studies; overall survival, n=3 studies). Thirteen percent of studies (n=6) failed to show clinical impact, that is 5 (16%) histoanatomic and 1 (7%) semiquantitative study(s), all published between 2000 and 2018 9–54 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies revealed significant prognostic impact (disease recurrence, n=6 studies; disease progression, n=18 studies; recurrence-free survival, n=6 studies; progression-free survival, n=13 studies; cancer-specific survival, n=7 studies; overall survival, n=3 studies). Thirteen percent of studies (n=6) failed to show clinical impact, that is 5 (16%) histoanatomic and 1 (7%) semiquantitative study(s), all published between 2000 and 2018 9–54 …”
Section: Resultsmentioning
confidence: 99%
“…Most studies on semiquantitative methods included in our comprehensive literature review summarizing over 3700 patients showed an association with progressionfree survival or cancer-specific survival. 12,18,32,[44][45][46][47][48]51,52 Only 7% of studies on T1 subcategorization failed to show such an association, 13,14,20,26,36,39,44 most of which applied histoanatomic methods. Studies, comparing head-to-head histoanatomic and semiquantitative methodology also revealed a better performance in terms of prognostic impact for the latter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, micrometric systems measuring the maximum extent of LP invasion at any direction overcome the anatomic issues and proved clinical significance. Interestingly, a recent retrospective study conducted on 73 patients compared 6 different substaging methods and showed that reporting the extent and/or the number of invasive foci represented the most practical approach not conditioned by orientation or artifacts [34]. The one proposed by Van Rhijn et al applies a 0.5 mm cut-off to classify tumors in T1m (microinvasive) and T1e (extensively invasive) [21].…”
Section: Discussionmentioning
confidence: 99%